Kebijakan Indonesia dalam Aspek Lingkungan dan Perdagangan: Studi Kasus Cantrang - Gita Karisma; Tety Rachmawati; Sanjaya, Fitri Juliana (Universitas Bosowa, 2020)
This research focuses on Indonesian's policy regarding the postponement of the prohibition of using cantrang and its relationship with trade and environmental aspects. In line with the trend trading which is draws many environmental issues as a rule, Indonesia should be careful to apply trade policy. One of them is the cantrang as a fishing tool which will affect Export of Indonesian Fishery Products. This research uses a qualitative approach with case studies. The results of this research show that cantrang is considered as fishing equipment damaging marine ecosystem, so that its restriction will give benefit for Indonesia. Indonesia has implemented a regulation prohibiting the use of cantrang in 2017 but Indonesia withdrew the regulation in 2018. This research finds out how the Indonesia policy tends to prioritize trade interests over environmental interests.